Association between body mass index and blood pressure among adults - Bindu Thapa; Deepti KC; Kalpana Shrestha; Sunita Gurung (Journal of Gandaki Medical College, 2022)
Introduction: Increase in body mass index increases risk of developing high blood pressure. Controversies have been found regarding the association of body mass index with high blood pressure. So, this study was conducted to find association between body mass index and blood pressure.